Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-93752-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold nanoparticles on the structure and neuroprotective function of protein L-isoaspartyl methyltransferase (PIMT)

Abstract: Fibrillation of peptides and proteins is implicated in various neurodegenerative diseases and is a global concern. Aging leads to the formation of abnormal isoaspartate (isoAsp) residues from isomerization of normal aspartates in proteins, triggering fibril formation that leads to neurodegenerative diseases. Protein L-isoaspartyl methyltransferase (PIMT) is a repair enzyme which recognizes and converts altered isoAsp residues back to normal aspartate. Here we report the effect of gold nanoparticles (AuNPs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…AuNPs are nanocarriers for intracellular drug or gene delivery. They have the characteristics of low toxicity, large speci c surface area, easy controllable surface assembly, and high speci city (Chatterjee et al 2021). Anand et al (Anand et al 2021) found that AuNPs surface-functionalized with a plant-based amino acid mimosine can attenuate Aβ brillization and neuronal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs are nanocarriers for intracellular drug or gene delivery. They have the characteristics of low toxicity, large speci c surface area, easy controllable surface assembly, and high speci city (Chatterjee et al 2021). Anand et al (Anand et al 2021) found that AuNPs surface-functionalized with a plant-based amino acid mimosine can attenuate Aβ brillization and neuronal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The activity assay was carried out as described previously using a SAM-510 colorimetric assay kit (G-Bioscience, ), as previously described . The reaction was carried out in 0.1 M Tris–HCl buffer (pH 7.2) using monomeric Aβ42 as substrate for PIMT.…”
Section: Methodsmentioning
confidence: 99%
“…In this connection, it may be mentioned that the enzymatic activity and consequently the antifibrillar function of PIMT can be boosted by the addition of gold nanoparticles (AuNPs), which was demonstrated by administering PIMT-AuNP conjugates to Aβ42-induced PC12-derived neurons, showing a much higher cellular survival of the derived neurons compared to PIMT alone. 42 There is thus the possibility of enhancing the potential of PIMT against the toxicity induced by AβO oligomers also.…”
Section: Visualization Of Aβo Using Afm and The Composition Of Oligom...mentioning
confidence: 99%
“…Based on these above findings, the authors proposed that the bacterial pathogens received a sufficient quantity of β-lactam antibiotic that could saturate the ESBLs, and at the same time, antibiotic molecules that remain untouched by ESBLs might start their usual action on cell wall synthesis. In addition, AuNPs have the inherent ability to alter the structure and function of enzymes via interacting with them [ 94 , 95 , 96 , 97 , 98 ]; thus, it might be speculated that AuNPs could interact with ESBLs enzyme directly and disrupt their function.…”
Section: Plausible Antibacterial Mechanism Of Aunpsmentioning
confidence: 99%